Hubungan Antara Persepsi Kualitas Pelayanan Dengan Minat Kunjungan Ulang Pasien Rawat Jalan Okupasi Terapi RS Ortopedi dr. R. Soeharso Surakarta 2009 - Yuliastuti, Tri; Arso, Septo Pawelas; Nugraha P, Priyadi (MEDIA KESEHATAN MASYARAKAT INDONESIA, 2010)
The number of therapist and patient visit of occupational therapy service of dr. Suharso Orthopedic Hospital(RSOS) is larger than other services in Surakarta. Visit number of existing patient is more than new patient,which it is mean that most of patients have willingness to revisit to get services. Quality of services in healthcare has important role in patient satisfaction and intention in repurchasing as customer. However, there arestill patient complaints toward the quality service of occupational therapy of RSOS. It’s need to evaluate theservice quality and patient intention of revisit. This research aim is to find out the correlation between patientperception of service quality and patient interest to go revisit occupational therapy room of RSOS. Thisresearch type was quantitative method with cross sectional approach. Population study was 205 patients, whowere visiting in January until April 2009. Data obtained by interview used questionnaire toward 34respondents by accidentally sampling method. Data analyzed use statistic test of pearson-product momentwith 95% confidence level. This research revealed that the most of patient perception of therapist servicesquality is good (64.7%), the most of perception of service equipment quality is good (64.7%) and the mostperception of therapy result is also good (61.8%). While 67.6% of patient revisit interest is . The statisticanalyzes showed that perception of service equipment quality (p=001) and perception of therapy result(p=0,036) have correlation with patient revisit interest. While therapist services quality (p=0,067) didn’t havecorrelation with patient revisit interest. It’s concluded that perception of service equipment quality andperception of therapy in RSOS are good and it’s influenced revisit patient.Keywords: Perception, Service Quality, Occupational Therapy.http://ejournal.undip.ac.id/index.php/mkmi/article/view/2839